Physicochemical Variation in Nanogold-Based Ayurved Medicine Suvarna Bhasma Produced by Various Manufacturers Lead to Different In Vivo Bioaccumulation Profiles - Snehasis Biswas MTech; Mukesh Chawda BAMS; Kapil Thakur PhD; Ramacharya Gudi MD; Jayesh Bellare PhD (SAGE Publishing, 2021)
Suvarna Bhasma (SB) is a gold particle-based medicine that is used in Ayurved to treat tuberculosis, arthritis and nervous diseases. Traditionally, the Ayurved preparation processes of SB do exist, but they are all long, tedious and involve several steps. Due to this, there is a possibility of bypassing the necessary Ayurved processes or non-adherence to all steps or use of synthetic gold particles. Our aim is to characterize 5 commercial SB preparations from 5 different manufacturers. A comparative physicochemical, pharmacokinetic (PK) and bioaccumulation study was carried out on all the 5 SB preparations. The general appearance such as color and texture of these 5 samples were different from each other. The size, shape and gold concentration (from 32-98 wt%) varied among all the 5 SBs. The accumulation of ionic gold in zebrafish and gold concentration profiles in rat blood were found to be significantly different for all the 5 SBs. Non-compartmental PK model obtained from the concentration-time profile showed significant differences in various PK parameters such as peak concentration (C max ), half-life (t 1/2 ) and terminal elimination slope (λ z ) for all the 5 SB preparations. SB-B showed the highest C max (8.55 μg/L), whereas SB-D showed the lowest C max (4.66 μg/L). The dissolution of ionic gold from SBs in zebrafish tissue after the oral dose had a 5.5-fold difference between the highest and lowest ionic gold concentrations. All the 5 samples showed distinct physicochemical and biological properties. Based on characteristic microscopic morphology, it was found that 2 preparations among them were suspected of being manufactured by non-adherence to the mentioned Ayurved references.